1985
DOI: 10.1557/proc-45-71
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Stopping Power for Low Energy Ions

Abstract: A procedure to be used in ion implantation calculations has been developed to determine the stopping power of an ion at low energy as a function of its effective charge. The ion effective charge accounts for screening of the ion and has been found to have considerable effect on the stopping power through its dependence on the target electron density.Steps in the procedure include: the calculation of the Fermi momentum of the target, calculation of the relative velocity between the projectile and target electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

1990
1990
1996
1996

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Later, a purely local version of the BK theory was developed to take into account the charge distribution of the electrons 43,44 . Comparison with other electronic stopping models, such as Lindhard and Scharff 4 , Firsov 45 , and the above nonlocal implementation 42 , showed a marked improvement in modeling electronic stopping in the channel 7,43,44 . Good agreement between simulated dopant profiles and the SIMS profiles for boron implants into 100 single crystal silicon was obtained.…”
Section: Bca Monte Carlo Simulation Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Later, a purely local version of the BK theory was developed to take into account the charge distribution of the electrons 43,44 . Comparison with other electronic stopping models, such as Lindhard and Scharff 4 , Firsov 45 , and the above nonlocal implementation 42 , showed a marked improvement in modeling electronic stopping in the channel 7,43,44 . Good agreement between simulated dopant profiles and the SIMS profiles for boron implants into 100 single crystal silicon was obtained.…”
Section: Bca Monte Carlo Simulation Resultsmentioning
confidence: 88%
“…First, in comparison with other electronic stopping models used in Monte Carlo simulations based on the MAR-LOWE platform, we stress that in our model the effective charge is a nonlocal quantity, neither explicitly dependent on the impact parameter nor on the charge distribution, and the stopping power for a proton depends on the local charge density of the solid. A purely nonlocal version of the BK theory was implemented into MARLOWE 42 , in which both the effective charge and the stopping power for a proton depend on a single nonlocal parameter, namely, the averaged one electron radius. Its results demonstrated that energy loss for well-channeled ions in the keV region has high sensitivity to the one-electron radius in the channel.…”
Section: Bca Monte Carlo Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…En un estado inicial la distribución de momentos en el plano de la superficie es una función delta, δ(E 0 ,v), dada por la energía de los iones E 0 y su dirección. El momento puede ser sustitudo por su energía E y elángulo θ si nos encontramos en un plano 6 . En cada paso del cálculo, la redistribución de las partículas en el espacio de momentos para una profundidad x y en un elemento dx se obtiene resolviendo la ecuación 3.70.…”
Section: Iones Paradosunclassified